Stress, burnout and coping in health professionals: a literature review - Costa, Bárbara (2018)
Context: Stress is a phenomenon inherent to life and it becomes inevitable, particularly in a professional context, having consequences on life quality. This is a disorder that affecting several people worldwide, namely health professionals, and is originated by various factors. Objective: The aims of this review article are studying, in the stress and burnout in health professionals in order to clarify the definition, identify the possible causes, related factors and identify the coping strategies. Methods: This review article was performed through data bases such as b-on, PubMed and books. It was used articles in Portuguese, English and Spanish and that corresponde to established descriptors. Results: Stress affects individuals from any age and professional area. When is caused by work complications is called of occupational stress. This phenomenon resultes of the action of an agent stressor that can be physical, social or even psychological. Other phenomenon is Burnout Syndrome, which is characterized by emotional exhaustion, lack of professional accomplishment and depersonalization. To mitigate the effects of stress, there are specific mechanisms of coping. Conclusion: Stress and burnout are quite prevalent phenomena among health professionals. As these professionals have a fundamental role in patient care it is extremely important that they feel well physically and psychologically, as to fulfill its functions well as caregivers. In this way, it becomes important to act in the relationship between the individual and the problem, improving the skills of encouraging to use his social and personal resources to obtain control over the circumstance inducer of stress.